Air traffic controller crossing event analysis for medium angle crossing - Lin, Ziyu (2019)
With advancements in Air Traffic Management (ATM) technologies foreseen to increase the dynamicity and complexity of airspace in the future, these changes will inadvertently lead to adverse impacts on Air Traffic Controllers’ (ATCO) monitoring performance. Previous incident reports have identified the lack of experience in ATCOs and complexity of airspace as reasons for their poor monitoring performance which ultimately led to the loss of separation of aircraft. There have been numerous research studies conducted to further understand the cognitive mental workload and tactical monitoring behaviour of ATCOs during radar surveillance. Previous research studies have also made use of eye-tracking technology and found that there are differences in the visual monitoring behaviour between subjects of different expertise levels. However, such studies are more often than not overly-simplistic in their approach and do not capture the entire complexity of an ATCO’s taskload. This study examines two commonly studied ocular metrics, fixation count and fixation duration, to investigate the visual monitoring behaviour of subjects from three different expertise levels (i.e. novice, intermediate and expert) at medium angle crossings. A novel concept of aligned fixation peaks, which are instances in which the subject looks at the aircraft pair-in-crossing above his or her average fixation count and duration threshold in the same time period, was developed to filter crossing monitoring events from en-route monitoring. After which, a crossing signature model was proposed to characterise the monitoring behaviour of each expertise level based on the concept of aligned fixation peaks. Overall, it was found that the mean fixation count and duration of aligned fixation peaks were generally higher for expert and intermediate compared to novice, while the mean fixation duration of aligned fixation peaks was generally higher for the intermediate compared to the expert group. A multiple linear regression model was also formulated to predict the total number of aligned fixation peaks for a subject based on two variables—the difference in the distance of airway travelled between the aircraft pair-in-crossing and duration of monitoring. In the future, these findings may serve as the foundation to help assess the monitoring performance of an individual at medium angle crossings and help improve ATCO training as well as maintain safety standards in an increasingly congested and complex airspace.